De.mem advances its hollow-fibre ultrafiltration and nanofiltration membrane technology. Issue 8 (August 2019) - Kroell, Andreas; Chua, David
Abstract : The introduction of different products supports De.mem Ltd's strategy of developing a portfolio of membranes, and helps to strengthen its customer-base and broaden revenue streams. In addition to licensing proprietary technologies, the Singaporean–Australian water and wastewater treatment business is actively pursuing proprietary technology by further advancing hollow-fibre ultrafiltration and nanofiltration membranes that it is developing in-house, as this article explains.